Design of Intelligent Transportation Inquiry System Based on MapX in the Environment of VC++ - Cheng Juan; Sun Lu (MATEC Web of Conferences, 2016)
This paper applied MapInfo, the professional soft ware tool of GIS, integrated secondary exploiture combining with elctronic maps, and made use of the exploiture flat roof Visual C++ as the tool of visualize development, transferred MapX, a control of MapInfo, integrated them. The paper designed the Inquiry System in Intelligent Transportation, which including query system of road information, query system of bus information, query system of district information. It can be carried out space analysis and query function based on GIS. Adopted SQL Server manage attribute data, by data binding, attribute data in SQL Server and victor picture data were combined.